NURSES' ROLE IN PAIN RELIEF DURING LABOR: INTEGRATIVE REVIEW ON NON-PHARMACOLOGICAL METHODS (REMUNOM, 2025)
Childbirth care should be planned from prenatal care onwards, prioritizing humanized and non-pharmacological practices that guarantee women's autonomy, allowing them to make informed choices and actively participate in the process, which contributes to a more positive and empowering experience. This study aims to investigate what has been published in the literature on the role of nurses in caring for pregnant women to relieve pain during labor using non-pharmacological methods. This is an Integrative Literature Review study. The guiding question was: What have been the nurses' interventions for pain relief during childbirth care? For the search, sources from the Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (Medline via PubMed), Scientific Electronic Library Online (SciELO) and Web of Science were selected, as well as articles published from 2020 to 2024, in Portuguese. Initially, 4,840 articles were found, of which seven articles were approved as meeting the inclusion criteria for this review. The main results reveal a comprehensive perspective on the role of nurses in the use of non-pharmacological methods (NPM) for pain relief during labor, highlighting both the progress achieved and the difficulties still existing in this developing field. The evidence indicates an increasing recognition of these approaches, although there are still barriers that need to be overcome for their application to be more effective. It is concluded that non-pharmacological methods represent effective and humanized strategies for pain relief during labor, strengthening female protagonism. The role of nurses is fundamental in this context, promoting comprehensive care and continuous support for pregnant women. However, the consolidation of these practices requires investment in professional training, adequate structure and greater emphasis on prenatal care.